Odpowiedzi

2010-02-28T15:34:55+01:00
A) 3(x - 2y) + x(x + 2y - 1) - 2y(x +y - 2)= dla x= -½, y= -3
=3x-6y+x²+2xy-x-2xy-2y²+4y=
=2x-2y+x²-2y²

2x-2y+x²-2y² = 2*(-½)-2*(-3)+(-½)²-2*(-3)² = -1+6+¹/₄ -18 = -13+¹/₄ = -12 ¾


b) 2x(1 - b + a ) -3(3a - 2b - 3) -2b(b - a + ½)= dla a= -1 b=2
=2x-2xb+2xa-9a+6b+9-2b²+2ab-b=
=2x-2xb+2xa-9a+5b+9-2b²+2ab

2x-2xb+2xa-9a+5b+9-2b²+2ab= 2x-2x*2+2x*(-1)-9*(-1)+5*2+9-2*2²+2*(-1)*2 = 2x-4x-2x+9+10+9-8-4 = -4x+16

-4x+16 = 0
-4x = -16/:(-4)
x = 4
2010-02-28T15:40:05+01:00
A) 3(x - 2y) + x(x + 2y - 1) - 2y(x +y - 2)= dla x= -½, y= -3=
3( -½- 2*-3) -½ ( -½+ 2*-3 - 1) - 2*-3( ½-3- 2)=-1+6+¹/₄ -18 = -13+¹/₄ = -12 ¾

b) 2x(1 - b + a ) -3(3a - 2b - 3) -2b(b - a + ½)= dla a= -1 b=2=
= 2x-4x-2x+9+10+9-8-4 = -4x+16
-4x = -16/:-4
x = 4


Ps mam nadzieje że pomogłam ;)